Acceptance : a memoir - Nietfeld, Emi (Penguin Press, 2022)
"A brilliant, funny, generation-defining memoir about the double bind of crafting perfect adversity narratives for highly selective institutions, while fumbling through the far murkier reality of actual life in foster care and inpatient mental health treatment. As a child, Emi Nietfeld was caught between a hoarder mother who got her put on antipsychotic medication, but was also the only person to believe she was exceptional, and a state system exemplified by a foster mom who tried to ban her art history flash cards because they had naked pictures (of Michelangelo's David). Even after wresting free of grim inpatient mental health institutions and getting into a prestigious boarding school, Emi scrambled for places to sleep during breaks. Realizing that her path to true independence lay in reinventing herself as a talented overcomer deserving of a full ride, she became obsessed with college admissions. While taking on the sad challenge of presenting herself as resilient to gain authorities' approval, Emi lived the untidy version of actual adversity at the same time--literally drafting her Common App statement while living out of her '92 Corolla. She found herself "trading my past for my future" in college admissions essays and scholarship applications, in an extreme example of the immense pressure on teenagers from all backgrounds to build the foundations of their entire lives. Emi's story is a harsh illumination of the near-impossible challenge set by societal expectations of coming from nothing, the brokenness of our child welfare system, and the reality that congratulatory letters from top schools couldn't keep her safe - as she found when she was raped while on a trip following her Harvard admission. Though Emi learns that entering the Ivy League, working in Big Tech, and living in a fancy apartment doesn't mean her life turns into gold, her reflections on her unlikely history, and her journey in confronting trauma and injustice, hold powerful lessons. Candid and frequently harrowing, with a ribbon of dark humor, Acceptance is a stunning human story and an invaluable view of the actual cost of upward mobility"--